Preclinical Pharmacokinetics and First-in-Human Pharmacokinetics, Safety, and Tolerability of Velpatasvir, a Pangenotypic Hepatitis C Virus NS5A Inhibitor, in Healthy Subjects - Mogalian, Erik; German, Polina; Kearney, Brian P.; Yang, Cheng Yong; Brainard, Diana; Link, John; McNally, John; Han, LingLing; Ling, John; Mathias, Anita (Antimicrobial agents and chemotherapy, 2017)
Preclinical characterization of velpatasvir (VEL; GS-5816), an inhibitor of the hepatitis C virus (HCV) NS5A protein, demonstrated that it has favorable in vitro and in vivo properties, including potent antiviral activity against hepatitis C virus genotype 1 to 6 replicons, good metabolic stability, low systemic clearance, and adequate bioavailability and physicochemical properties, to warrant clinical evaluation. The phase 1 (first-in-human) study evaluated the safety, tolerability, and pharmacokinetics of VEL in healthy human subjects following administration of single and multiple ( n = 7) once-daily ascending doses and of VEL in the presence and absence of food. Following administration of single and multiple doses, VEL was safe and well tolerated when administered at up to 450 mg and when administered with food. The pharmacokinetic behavior of VEL observed in humans was generally in agreement with that seen during preclinical characterization. Following administration of multiple doses, VEL trough concentrations were significantly greater than the protein-adjusted half-maximal (50%) effective concentration of VEL against HCV genotype 1 to 6 replicons at all evaluated doses greater than 5 mg. The pharmacokinetics of VEL were not significantly affected by administration with food. Collectively, the results of this study support the further clinical investigation of VEL administered once daily as part of a regimen with other pangenotypic direct-acting antivirals for the treatment of HCV infection.